The dead I know - Gardner, Scot (Houghton Mifflin Harcourt, 2015)
Aaron Rowe's new job at a funeral parlor may be his salvation from sleepwalking, dreams he can not explain and memories he can not recover, but if he does not discover the truth about his hidden past soon, he may fall asleep one night and never wake up.